Population Estimation of Double–Spotted Gecko, Gekko monarchus (Sclegel, 1836) at 5 Regency in Bengkulu Province - Atmaja, Vesti Yunisya; Parlindungan, Deni; Sipriyadi, Sipriyadi; Sinaga, Fery Fernando; Saputri, Ika; Novianti, Reti; Priadi, Untung; Gusti, Widia (Universitas Labuhanbatu, 2022)
The Double–Spotted Gecko (Gekko monarchus) is one of the reptiles on the list of wild animals given an annual utilization quota for their capture in the wild. Bengkulu Province, as one of the distribution place of G. monarchus does not yet have data on its population. The research was conducted on 13 November to 2 December 2021, using two methods: interviews with the community and a Visual Encountered Survey at night. The research area in the five districts is 61.49 ha, the number of houses visited is 433, and the number of people interviewed is 386. The number of geckos counted in the interviews was 315, while from direct observation, there were 275. Geckos were most found at house and dominated (41.2%) by hiding between wooden walls. Based on the results of extrapolation calculations, the population estimates for the Double–Spotted Gecko are North Bengkulu 43,720–54,427 individuals; Mukomuko 32,997–51,810 tails; Central Bengkulu 6,248–9,187 individuals; Total 39,883–72,720 individuals; and South Bengkulu 11,469–11,592 individuals.